Chemical dynamics from the gas‐phase to surfaces. Issue 1 (19th May 2021) - Auerbach, Daniel J.; Tully, John C.; Wodtke, Alec M.
Abstract: The field of gas‐phase chemical dynamics has developed superb experimental methods to probe the detailed outcome of gas‐phase chemical reactions. These experiments inspired and benchmarked first principles dynamics simulations giving access to an atomic scale picture of the motions that underlie these reactions. This fruitful interplay of experiment and theory is the essence of a dynamical approach perfected on gas‐phase reactions, the culmination of which is a standard model of chemical reactivity involving classical trajectories or quantum wave packets moving on a Born–Oppenheimer potential energy surface. Extending the dynamical approach to chemical reactions at surfaces presents challenges of complexity not found in gas‐phase study as reactive processes often involve multiple steps, such as inelastic molecule‐surface scattering and dissipation, leading to adsorption and subsequent thermal desorption and or bond breaking and making. This paper reviews progress toward understanding the elementary processes involved in surface chemistry using the dynamical approach. Key points: The fruitful interplay between chemistry and physics leads to an atomic scale view of reactions taking places at catalytically active surfaces. Improved observations of chemical reactions taking place in complex environments drive the development of new approaches to theoretical chemistry. Complex reaction networks from real catalysts are boiled down to their elementary steps and examined from first principles. Abstract : The Dynamical Approach to surface chemistry relies on the fruitful interplay between experiment and theory. By developing first principles models that successfully explain dynamics experiment, we can examine the detailed atomic motion involved in chemical processes. Here is an image representing a trajectory of H atoms colliding with a graphene surface forming a transient C‐H bond. The dynamical approach allows us to understand the sticking of H atoms to graphene surfaces and more generally the nature of the interactions during the collisions. Here, the H atom approach triggers an electronic change to the system within about 10 femtoseconds, where the attacked C‐atom in the graphene experiences partial electronic re‐hybridization from sp 2 to sp 3 . Of course, this also affects the electronic bonding to its neighbors. The fastest response to this electronic change is to excite in‐plane C‐C stretching. In fact, it is the next nearest neighbor C‐atoms (and not the C‐atom being attacked by the H atom) that begin moving first. Only later does the H‐attacked C‐atom begin to pucker out of plane, exerting a drag on the departing H atom.The transfer of energy to these four atoms accounts for most of the large energy loss observed in experiment.